Photographic representations of violence after the 1906 Valparaíso earthquake (Chile) - Palavecino Sepúlveda, Gian (2021)
The Valparaíso earthquake in 1906 destroyed the city almost entirely. As a result, the authorities used public execution as a method to maintain the stability of the city, and these punishments were photographically recorded. From this context, the paper objective is to study the photographs that appears in the magazines Zig-Zag and Sucesos, the book La catástrofe del 16 de Agosto de 1906, and 4 photographic albums. The images have been categorized in the following subjects: 1) violence; 2) authority; 3) fiscality. The text proposes that the images published after the earthquake, could have been used for the construction of a discourse of power that, while recalling the leading’s groups as saviors of the city, legitimized the power of the authorities, building a historical memory from the self-representation of the elites versus the image of the popular sectors.